Budget wise / Fatin Aqilah Mohd Jaafar … [et al.] - Mohd Jaafar, Fatin Aqilah; Mazli, Farah Eizlin llyana; Razali, Nurafarina; Ahmad, Nurul Amirah; Mohd Rafien, Nor Shahrina (Division of Research and Industry Linkages, 2017)
According to the economic status today, people are spending more than their saving. Poor financial management resulted in more than 25 000 Malaysians under the age of 35 being declared bankrupt between 2011 and 2017, according to the Malaysian Financial Planning Council (MFPC). Budget Wise app is one of the templates in PowerApps. In this template, we can create the budget for our organization or our personal life, You can edit the required data with the help of many functions in this template.